Chemical modulation of the metabolism of an endophytic fungal strain of Cophinforma mamane using epigenetic modifiers and amino-acids - Pacheco Tapia, R.; Vásquez Ocmín, Pedro; Duthen, S.; Ortíz, S.; Jargeat, P.; Amasifuen Guerra, Carlos Alberto; Haddad, Mohamed; Vansteelandt, Marieke (El Sevier, 2022)
10 páginas